Rancang Bangun Sistem Keamanan Ruang Persandian Menggunakan RFID dan Sensor PIR Berbasis IOT - Eni Muhadi; Sulartopo Sulartopo; Danang Danang; Dani Sasmoko; Nuris Dwi Setiawan (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
This Space Security System is a system that utilizes the existing Internet Network to monitor a room remotely or from a different location. With the aim of making it easier to limit employee access rights and monitor the presence of people in the room.So the author made a room security system tool using the Internet of Things (IOT) which was implemented at the Demak Regency Communication and Information Service. The way this system works is only employees who have access rights who can enter the room by attaching an RFID card to the RFID Reader sensor, and the way the PIR sensor works is to monitor human presence, when there is infrared or human emission it will send data to the web if it is in the room has people and the red LED lights up and the buzzer sounds, while the push button button is when the push button button is pressed the solenoid will open. By making this design, it will help improve room security at the Demak Regency Communication and Information Service, especially the Encryption Room